The Gravity Hypothesis and Transportation Cost Minimization - John M. Hartwick (Queen's University, Department of Economics, 1972)
The Hitchcock-Koopmans transportation problem is linked to the gravity model of regional analysis with the aid of two new analytical results. Eighty transportation problems are generated by Monte Carlo methods and solved by linear programming. The transportation cost minimizing flows are compared with the flows generated by gravity methods in least squares regressions and in other non-parametric tests. Flows generated by gravity methods are indicated to be relatively poor proxies for those generated in a transportation cost minimizing system.
Keywords: 330